Effectiveness of Implementing the Jigsaw Model in Learning Living Things in Improving Students' Learning Achievement in Class 9-1 Mts Dayah Al-Furqan Bambi in the 2024-2025 Academic Year - Linawidar, Linawidar (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
The learning process using the Jigsaw learning model in studying living things has an impact on learning planning, learning actions and learning observations that can improve student learning achievement. The purpose of this learning is to improve student learning achievement in studying living things. The subjects of this study were students of Class 9-1 MTs Dayah Al-Furqan Bambi in the 2024/2025 Academic Year. A total of 15 students, consisting of 9 boys and 6 girls. The procedure of this research is to carry out planning, action, observation and reflection. cycle I Meeting 1 observation on the learning process aspect turned out that the learning process reached the criteria of less good at a value of 2. The average research results on students' communication abilities were 1.7 collaboration 1.8, innovation 1.7 and critical 1.7. For the completeness of student learning potential reached 46% complete. Student learning scores were presented on average assessment of the affective aspect C, cognitive 6.4 psychomotor 6.4 classical learning completeness scores reached 26.7%. The second meeting yielded an average preliminary score of 4 (good), core activities (4), and closing activities (4) with an average score of 4. The criteria were good. Students' learning potential scores were: communication skills (2.2, poor), collaboration skills (2.8, approaching fair), innovation skills (2.6, approaching fair), and critical thinking skills (2.2, poor). The students achieved 87.7% completeness in their learning potential. They achieved a B in affective skills, a B in cognitive skills, and a B in psychomotor skills. The learning completeness score reached 80% completion in the classroom